Modulation of murine blastocyst hatching in vitro by glutamine and tryptophan (2011)
ABSTRACT: Enrichment of culture media with amino acids improves embryo development. However, little is known about the specific action of each amino acid during embryogenesis. The present study was undertaken to examine the effect of L-glutamine (Gln) and tryptophan (Trp) on mouse embryo hatching, expansion and viability in vitro. Blastocysts were collected from 6- to 8-week-old female BALB/c mice (N = 30) and cultured in M2 medium containing either 0.125, 0.25 or 0.5 mM Trp, 1 mM Gln, or M2 alone. Gln significantly increased (100%; P < 0.05) blastocyst hatching at 24 h compared to M2 alone or Trp; moreover, Trp inhibited blastocyst hatching when compared to M2 alone (P < 0.05) at 72 h. In contrast, the percentage of embryos reaching the state of expanded blastocyst at 48 h was significantly higher in medium with 1 mM Gln (66.6%; P < 0.05) or with 0.125 mM Trp (61.1%; P < 0.05). Unexpectedly, Trp increased the percentage of degenerated blastocysts after 48 h (67.7%; P < 0.05), while Gln preserved blastocyst viability. These results suggest that Gln may enhance blastocyst hatching, expansion and viability in vitro.